Characterization of silver carp myosin glycated with phosphorylated konjac oligo‐glucomannan. (8th May 2021) - Zhang, Jianyou; Zhou, Wei; Xu, Mingjiang; Fang, Chunhua; Du, Qiwei; Xu, Xia; Lyu, Fei; Ding, Yuting; Liu, Jianhua
Abstract: BACKGROUND: Myosin (Ms) is abundant in fish meat, but it has limited application in the food industry because of its low solubility and thermal stability. Our previous reports found that these functional properties of Ms can be significantly improved after glycation with konjac oligo‐glucomannan (KOG). However, the effects of phosphorylated KOG (PKOG) on physicochemical, structural and functional properties of silver carp Ms are still unknown. RESULTS: This study characterized the silver carp Ms protein glycated with PKOG at 50 °C and 75% relative humidity for 48 h. As degree of phosphorylation increased, free amino content increased, whereas degree of grafting decreased. Meanwhile, isoelectric point (p I ) reduced, however, PKOGs showed no differences in p I . Sodium dodecyl sulfate–polyacrylamide gel electrophoresis analysis suggested the formation of glycoconjugates, and scanning electron microscopy revealed thinner flakes and uneven appearance of glycoconjugates. Fourier transform infrared spectroscopy indicated that the amide I, II and III bands of Ms were changed by the glycation. Ms became highly soluble in 0.5 mol L −1 NaCl with increased phosphate addition in PKOGs. Thermal stability of Ms was effectively improved when heated at 80 °C for 60 min. CONCLUSION: Glycation with appropriate PKOG might be a promising method for Ms modification because of the resulting improvement in solubility and thermal stability. © 2021 Society of Chemical Industry.